The impact of climate change on maize production: Empirical findings and implications for sustainable agricultural development - Zhang, Zhexi; Wei, Jiashuo; Li, Jinkai; Jia, Yuankai; Wang, Wei; Li, Jie; Lei, Ze; Gao, Ming (Frontiers in Environmental Science, 2022)
Continuous warming climate conditions have triggered numerous extreme weather events, exerting an unprecedented impact on agricultural and food production. Based on the panel data of 3,050 small farmers engaged in maize planting from 2009 to 2018 and collected by the National Rural Fixed Observation Point in China, this study uses the Transcendental Logarithmic Production Function model to estimate the impact of temperature, precipitation, and sunshine hours on maize output. Further, considering climate condition heterogeneity, this study analyzes the development potential of five major maize production areas in China. Results show that temperature and precipitation have a positive impact on maize output and that insufficient sunshine hour is an obstacle to the growth of maize output. Five major maize production areas are affected by climate condition differently, entailing the need for tailored response measures. Additionally, land, labor, and material capital input are key factors affecting maize output. Based on conclusion, we put forward the following suggestions to promote sustainable agricultural production, including strengthening the prediction of temperature, precipitation, and sunshine hours in major maize production areas, optimizing the agricultural production layout and the planting structure based on local endowment, enhancing farmers’ adaptive behavior training toward climate change, developing irrigation and water conservation projects.